Influence of Sex and Mother Tongue on Academic Performance - Olmedo Ruiz, Francisco J. (2020)
This work focuses on knowing the differences in the academic performance of children’s education students according to sex and mother tongue. To this end, and starting from the different scenarios presented by multiculturality, we have taken into account the peculiarities of this cultural diversity reflected in the classroom. On the basis that we are in a context in which an official language and a cultural dialect coexist. The sample consisted of 489 children’s education students from 12 public educationalestablishments and 3 concerted centres, aged 5 to 6 (M= 5.23; DT= 506), of which 51.4 percent were boys (n=249) and 48.6 percent girls (n=235) of which 37.7% had Spanish as their mother tongue (n=183) and 62.3% Darija (n=302). The multidimensional instrument of basic skills in Child Education was used (Mateos y Olmedo, 2018). The results of ANOVA analysis and binary logistic regression showed that the mother tongue is the main cause of these children’s differences, negatively affecting those who have mother tongue Castilian, being clearly defined that the main weakness is shown in the areas of oral expression, written expression and phonetic consciousness.